Điều chế cấu trúc của 5-{[4-[(5-mercapto-1,3,4-thiadi-azol-2-yl) amino] Phenyl} Phenyl] amino}1,3,4-thiadi-azol-2-thioll) - Hùng, Trần Văn; Hoa, Trần Thị Kim; Hồng, Ngô Phương; Phú, Phùng Hữu (VNU Journal of Science: Natural Sciences and Technology; Vol 22 No 3, 2006)
Abstract